Pharmacokinetic parameters and tissue distribution of magnetic Fe(3)O(4) nanoparticles in mice - Wang, Jun (Dove Medical Press, 2010)
BACKGROUND: This study explored the pharmacokinetic parameters and tissue distribution of magnetic iron oxide nanoparticles (Fe(3)O(4) MNPs) in imprinting control region (ICR) mice. METHODS: The Fe(3)O(4) MNPs were synthesized by chemical coprecipitation, and their morphology and appearance were observed by transmission electron microscopy. ICR mice were divided into a control group and a Fe(3)O(4) MNP-treated group. Probable target organs in ICR mice were observed, and the pharmacokinetic parameters and biodistribution of Fe(3)O(4) MNPs in tissues were identified using atomic absorption spectrophotometry. RESULTS: Fe(3)O(4) MNPs were spherical with a well distributed particle diameter, and were distributed widely in various target organs and tissues including the heart, liver, spleen, lungs, kidneys, brain, stomach, small intestine, and bone marrow. The majority of Fe(3)O(4) MNPs were distributed to the liver and the spleen. Fe(3)O(4) MNP levels in brain tissue were higher in the Fe(3)O(4) MNP-treated group than in the control group, indicating that Fe(3)O(4) MNPs can penetrate the blood–brain barrier. CONCLUSION: These results suggest that the distribution of Fe(3)O(4) MNPs was mostly in the liver and spleen, so the curative effect of these compounds could be more pronounced for liver tumors. Furthermore, Fe(3)O(4) MNPs might be used as drug carriers to overcome physiologic barriers.